Experimental and theoretical study on hygrothermal long-term performance of outer assemblies in lightweight passive house. (January 2018) - Radon, Jan; Was, Krzysztof; Flaga-Maryanczyk, Agnieszka; Schnotale, Jacek
The article presents results of long-term experimental study of hygrothermal performance of envelope assemblies in a passive house located in Boruszowice (Southern Poland). The building was constructed in 2010 using prefabricated, lightweight technology. The construction of the walls and roof had been carefully planned to test both traditional solutions with higher thermal insulation and modified ones to improve the hygrothermal performance. Altogether, eight different walls and two roof constructions were integrated into the building structure and tested from the beginning of 2011 to the end of 2015 under real climate and usage conditions. In all assemblies, temperature was measured in three and relative humidity in four points at the surface and inside. Inner climate was measured by thermohygrometers installed in the rooms and outer climate was recorded by a weather station located near the building. Theoretical calculations were made using WUFI ® Plus software. Based on experimental and calculation results, the main hygrothermal phenomena depending on construction specifics and used materials are presented.